Mickel, J. T. y A. R. Smith. 2004. The pteridophytes of Mexico. Memoirs of the New York Botanical Garden 88: 1-1054 - Tejero-Díez, J. Daniel; Pacheco, Leticia (Instituto de Ecología, A.C., 2022)
Reseña de libro.